The combined effect of Al-5Ti-1B and Al-10Sr on the metallurgical properties of LM6 Al-Si sand castings - Lim, Y. P.; Sulaiman, Shamsuddin; Hamouda, Abdel Magid Salem; Megat Ahmad, Megat Mohamad Hamdan (Universiti Putra Malaysia Press, 2005)
Al-5Ti-1B is one of the prevalent grain refiners for Al-Si alloys in casting industry; on the other hand, Al-10Sr is one of the effective modifiers for Al-Si alloys. Grain refiners serve the purpose of refining the grain size of solidified castings while modifiers such as sodium and strontium are added to change the morphology. A hybrid modifier consists of 0.5wt% Al-5Ti-1B and Al-10Sr respectively has been formulated and inoculated into the melt of hypoeutectic LM6 Al-Si alloy to produce a slab casting by CO2 sand casting process. The geometry of the casting is purposely designed to have different thicknesses so as to induce directional solidification. This research work is aimed to study the combined effect of grain refiner and modifier on the metallurgical properties of LM6 sand castings. The significant finding is that a nearly full eutectic solidification is achieved in the casting. The cooling rates are also observed to be faster than those of solely grain-refined and original unmodified LM6 castings. The hardness is not significantly improved but the ultimate tensile strength can be further improved by 3.7% compared to that of castings grain-refined by 0.5wt% Al-5Ti-1B. The strain at UTS is significantly improved by 188% indicating better ductility. The metallographic observations show that the SDAS is coarser, but the eutectic phase is finer and in fibrous form in the Sr-modified LM6 castings.